Diabetes care: Comparison of patients' and healthcare professionals' assessment using the PACIC instrument. Issue 4 (2nd March 2017) - Gijs, E.; Zuercher, E.; Henry, V.; Morin, D.; Bize, R.; Peytremann‐Bridevaux, I.
Abstract: Rationale, aims and objective: Whereas the Patient Assessment of Chronic Illness Care (PACIC) instrument measures the extent to which care received by patients is congruent with the Chronic Care Model, the 5As model emphasizes self‐management and community resources, 2 key components of the Chronic Care Model. We aimed at comparing evaluation of diabetes care, as reported by patients with diabetes and healthcare professionals (HCPs), using these instruments. Methods: Two independent samples, patients with diabetes ( n = 395) and HCPs (including primary and secondary care physicians and nurses; n = 287), responded to the 20‐item PACIC and the six 5As model questions. The PACIC‐5A (questions scored on a 5‐point scale, 1 = never to 5 = always) was adapted for HCPs (modified‐PACIC‐5A). In both samples, means and standard deviations for each question as well as proportions of responses to each response modality were computed, and an overall score was calculated for the 20‐item PACIC. Results: Patients' and HCPs' overall scores were 2.6 (SD 0.9) and 3.6 (SD 0.5), respectively, with HCPs reporting higher scores for all questions except 1. Patients' education and self‐management, referral/follow‐up and participation in community programs were rated as low by patients and HCPs. Conclusion: Healthcare professionals, particularly diabetes specialists, tended to report better PACIC scores than patients, suggesting that care was not reported similarly when received or provided. Evaluation differences might be reduced by a closer collaboration between patients and HCPs, as well as the implementation of community‐based interventions considering more patients' perspectives such as patients' education and self‐management.